Prosodic effects on the planning of inserted /ɹ/ in Australian English. (July 2018) - Yuen, Ivan; Cox, Felicity; Demuth, Katherine
Highlights: Use of /ɹ/ insertion decreased when a foot boundary straddles V1.V2 hiatus. Complementary distribution between /ɹ/ insertion and glottalization. No difference in usage of /ɹ/ insertion between linking and intrusive environments. A foot boundary reduced the normalized F3 minimum of inserted /ɹ/. Inserted /ɹ/ triggered anticipatory F3 lowering at 10% of V1. Large anticipatory F3 lowering with the foot boundary most distant from the hiatus. Against the phonetic transition view, Inserted /ɹ/ and V1 must be planned in advance. Abstract: V1 .V2 hiatus is disallowed in many languages. In several varieties of English, when V1 is non- high, hiatus may be resolved by glottalization or /ɹ/ insertion. However, it is not well understood why speakers choose one over the other. In addition, questions remain about how foot boundary influences the hiatus-breaking strategy and whether perceived /ɹ/ is a phonetic transition or segmental insertion. Using an elicited production task, we investigated the effect of foot boundary on hiatus resolution and examined whether perceived inserted /ɹ/ exerts co-articulatory influence on V1 onset as predicted if it is segmental. Hiatus contexts were constructed from two types of coda-less nouns to generate V1 (e.g. paw without orthographic 'r', door with orthographic 'r') followed by one of three onset-less prepositions (' under ', ' above ', ' of '). Foot boundary locations were manipulated in three metrical conditions to examine gradient influence of foot boundary proximity (e.g. 'This is the [ paw ] under the dog', 'This is the [ paw a ] bove the dog', 'This is the [ paw of the] dog'). Results showed complementarity between glottalization and /ɹ/ insertion. Expanding the distance between the hiatus and foot boundary increased the use of /ɹ/ and decreased glottalization. F3 lowering at V1 onset occurred in perceived /ɹ/ contexts, providing acoustic evidence for inserted segmental /ɹ/.